Durability and versatility of free lattismus dorsi muscle flap in leg defects in tertiary care hospital - Islam, Abu Faisal M. Ariful; Ahmed, M. Iqbal; Uddin, M. Salah; Hamid, M. A. (International Surgery Journal, 2021)
Reconstruction of the legs and feet is challenging. Because of the composite tissue defects, inadequate and tight local tissues and poor circulation, soft tissue scarcity around the lower portion of the leg presents a significant challenge to the reconstructive surgeon. The aim of this study was to assess the outcome of free Lattismus dorsi (LD) muscle flap used for soft tissue reconstruction of leg defects. This prospective non-randomized study was conducted on 13 patients with leg defects of different causes attended emergency unit and outpatient clinic of plastic surgery department of plastic surgery and burn unit, Dhaka medical college hospital (DMCH) in the period between July 2017 and June 2018. Durability of coverage, flap success, infection and overall satisfaction were studied. The age distribution of the study population highest number of patients (46.15%) were in middle (31-40 years) age group whereas lowest are in older group (>51 years). Highest number of patients (84.61%) were standard myocutanous type of flap whereas lowest were in (15.31%) were chimeric flap and partial latissimus muscle flap. There were one case of total flap loss. Two patients had seroma formation among them one patient had partial necrosis. The outcome of reconstruction of n=13 patients 76.92% patients discharged with excellent recovery, (15.38%) patients discharged with good outcome, 1 (7.69%) patients had total flap loss. Flap is easy to dissect, anatomical variation is rare, long pedicle length which allow to anastomose with suitable recipient artery and finally donor morbidity is negligible.